2020
DOI: 10.1038/s42003-020-0990-5
|View full text |Cite
|
Sign up to set email alerts
|

Barley sodium content is regulated by natural variants of the Na+ transporter HvHKT1;5

Abstract: During plant growth, sodium (Na+) in the soil is transported via the xylem from the root to the shoot. While excess Na+ is toxic to most plants, non-toxic concentrations have been shown to improve crop yields under certain conditions, such as when soil K+ is low. We quantified grain Na+ across a barley genome-wide association study panel grown under non-saline conditions and identified variants of a Class 1 HIGH-AFFINITY-POTASSIUM-TRANSPORTER (HvHKT1;5)-encoding gene responsible for Na+ content variation under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…While there is increasing debate for crop plants surrounding leaf ion exclusion as a key tolerance mechanism (e.g. Houston et al 2020), there is consensus that grapevine shoot salt ion exclusion is an economically important trait for the grape and wine industry, to limit salt concentration in wine.…”
Section: Mechanisms Of Salt Tolerance In Grapevinementioning
confidence: 99%
See 1 more Smart Citation
“…While there is increasing debate for crop plants surrounding leaf ion exclusion as a key tolerance mechanism (e.g. Houston et al 2020), there is consensus that grapevine shoot salt ion exclusion is an economically important trait for the grape and wine industry, to limit salt concentration in wine.…”
Section: Mechanisms Of Salt Tolerance In Grapevinementioning
confidence: 99%
“…All grapevine HKT s, except non‐functional HKT1;3, had allelic variations that resulted in differences in Na + current magnitudes and rectification. Likewise, it has also been suggested that the expression level differences of HKT1 s, allelic variations and single amino acid residue changes could contribute to differences in shoot Na + exclusion capacity in Arabidopsis (Rus et al 2006, Ali et al 2020), rice (Cotsaftis et al 2012), wheat (Xu et al 2018, Borjigin et al 2020) and barley (Van Bezouw et al 2019, Houston et al 2020), as was observed for HKT1;1 in grapevine.…”
Section: Mechanisms Of Salt Tolerance In Grapevinementioning
confidence: 99%
“…In terms of the ionic component of salinity tolerance, Hazzouri et al [12] performed an association mapping study, where a USDA mini-core barley collection was screened for salinity tolerance under field conditions. A locus associated with leaf sodium content was identified on chromosome 4HL; the suggested candidate gene was HKT1;5, a high-affinity potassium transporter [12][13][14]. The increased salinity tolerance may be achieved by HKT1;5 retrieving Na + from the xylem sap at the root level, which would prevent Na + from accumulating in the shoot [12,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly artificially induced mutations in TmHKT1;5-A, which occurred during cloning of the gene, were shown to disrupt Na + transport properties in X. laevis, but this was not linked to a plant phenotype (Xu et al, 2018). A similar natural HKT1;5 variant (L189P) has recently been identified in barley accessions accumulating high grain Na + concentration, which also lacked the ability to transport Na + in X. laevis oocytes and was similarly shown to be on internal subcellular structures (Houston et al, 2020).…”
Section: Discussionmentioning
confidence: 99%